Sistem Informasi Pengalokasian Biaya Bahan Baku dengan Metode Harga Pokok Pesanan pada PT. Dian Karya Estate - Nining Rahaningsih; Raditya Danar Dana; Nana Suarna; Sri Muflikah Kurniarti (Universitas Maso'em Bandung, 2021)
Raw material costs are an important part of company operations, so we need a system that can accurately present raw material cost data which will be used as consideration for the company in making decisions. The system that is currently running at Kinaya Residence still uses a manual system so it is difficult to find accurate information. Based on the results of preliminary research, it can be concluded that in processing raw material costs using the cost of order method with the following characteristics 1) The nature of production is intermittent depending on on orders received, 2) The shape of the product depends on the specifications of the customer, 3) Collection of production costs is done on the order cost card, 4) the total production cost is calculated after the order is completed, 5) The production cost per unit is calculated, by dividing the total production cost by the total units ordered, 6) Accumulated costs generally use normal costs, 7) Products that have been completed are immediately handed over to the customer. Then to design a raw material cost allocation system that uses traditional methods with the programming language used is Hypertext Preprocessor. With this information system for allocating raw material costs, it is hoped that the presentation of financial reports about raw materials in companies can be done easily, quickly and accurately.